Health-related quality of life in children with hemoglobin E-?-thalassemia with special reference to iron overload - Basu, Rajarshi; Adhya, Raju; Jana, Debarshi (Indian Journal of Child Health, 2019)
Background: Hemoglobin (Hb) E disease is the most common Hb variant in Southeast Asia. However, in India, it is prevalent in Eastern India and West Bengal, but relatively rare in rest of the country. Objective: The objective of the study was to study the quality of life (QOL) in Hb E/?-thalassemia children with special reference to iron overload. Materials and Methods: An analytical case–control study on Hb E/?-thalassemia children aged 8–12 years was conducted who were admitted in the thalassemia unit and outdoor basis from the departments of pediatric medicine and hematology. They were evaluated for a period of 1 year and the effect on the QOL was assessed with health-related QOL (HRQOL) score along with psychological assessment. Results: A total of 50 subjects were included in the study. The HRQOL was assessed by PedsQL 4.0 generic core scale along with parent proxy report and psychological assessment was done by childhood psychopathology measurement schedule score. It was found that QOL was significantly better when pre-transfusion Hb level was above 7 g/dl. Conclusion: We found that total summary QOL score was not statistically significant, but the physical domain of QOL score showed statistically significant better score when the duration of blood transfusion is less. Therapy should widen beyond drugs with adequate physical rehabilitation and emotional support.